DEVELOPMENT AND CHARACTERIZATION OF SOLID CU / CUSO4 REFERENCE ELECTRODES - Marysca Shintya Dewi; Sagir Alva; Wan Adil Wan Jamil (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
In this research, a solid Cu/CuSO4 reference electrode has been developed. In this development process, the Cu/CuSO4 solid reference electrode provided consists of two types, namely the Cu/CuSO4 I solid reference electrode (ERP Cu/CuSO4 I) and the Cu/CuSO4 II solid reference electrode (ERP Cu/CuSO4 II). ERP Cu/CuSO4 I was prepared using two layers, namely the Cu/CuSO4 layer and the cellulose acetate layer which were placed sequentially on the surface of the planar type Cu electrode. Meanwhile, ERP Cu/CuSO4 II was prepared using three layers, namely a layer of cotton fiber/cellulose acetate, a layer of Cu/CuSO4, and a layer of cotton/cellulose acetate placed in sequence on the surface of the planar type Cu electrode, where the CuSO4 layer is between the two layers of cotton/cellulose acetate. Both types of Cu/CuSO4 solid reference electrodes were characterized by testing DmV in various concentrations of KCl solution and ERP Cu/CuSO4 II has been produced as the best reference electrode for Cu/CuSO4 solids with a DmV value of 3.3 mV. Furthermore, ERP Cu/CuSO4 II was selected for characterization using cyclic voltammetry (CV) testing, response vs Cl sensor testing, and drif testing. In CV testing, ERP Cu/CuSO4 provides a voltammogram graph pattern similar to the Ag/AgCl reference electrode as a commercial reference electrode. Meanwhile, in testing the response vs sensor Cl, ERP Cu/CuSO4 II gave a Nernstian number value  of -50.1 mV/decade with a test range of 0.1-10-3 M. ERP Cu/CuSO4 II showed fairly good stability, namely with a drift value of 0.46 mV/minute which is achieved after the conditioning process after 12 minutes.